Distribution of Atta (Hymenoptera - Formicidae) in "terra-firme" rain forest of Central Amazonia: density, species composition and preliminary results on effects of forest fragmentation - Vasconcelos, Heraldo Luis de (Acta Amazonica, 1988)
One hundred and fourteen hectares of a "terra-fiirme" rain forest 70 km north of Manaus, Amazonas, Brazil, were surveyed for leaf-cutting ant colonies (Atta spp). One half of this area was in isolated forest fragments (surrounded by pastures or second growth) of two sizes1 and 10 ha. The other half was in non-isolated fragments (connected to a large parch of forest) of the same sizes. Only two species occured in this forestAtta sexdens sexdens L. and A. cepfhalotes L. The first was the most abundant species with a mean density of 0.35 colonies per ha. The mean density of A. cephalotes colonies was 0.03 per ha. The density of colonies was not significantly different between the isolated fragments and the continuous forest. Furthermore, the species composition did not change with isolation. However, pre-isolation data and long term monitoring are necessary to conclude that the isolation of a forest fragment has no effect upon Atta colonies. The non-uniform spatial distribution of Atta colonics within the "terra-firme" forest must be taken into account when selecting conservation areas in the Amazon, in order to preserve this important group of ants together with their native habitat.